Synthesis of 1,4-Diketones via Titanium-Mediated Reductive Homocoupling of α-Haloketones - Le, Nathan N.; Rodriguez, Aimee M.; Alleyn, James R.; Gesinski, Michael R. (Synlett, 2018)
1,4-Diketones have been synthesized via a reductive homocoupling of α-haloketones. Addition of a Grignard reagent to titanium(IV) isopropoxide affords a low-valent titanium(III) intermediate that is believed to mediate a radical dimerization reaction. The reaction works well for a variety of aromatic α-haloketones including heteroaromatic compounds.
Keywords: homocoupling; low-valent titanium; 1,4-diketone; radical dimerization; Kulinkovich reagent